Vascular Connections Into the Grape Berry: The Link of Structural Investment to Seededness - Xiao, Zeyu; Chin, Sabrina; White, Rosemary G.; Gourieroux, Aude M.; Pagay, Vinay; Tyerman, Stephen D.; Schmidtke, Leigh M.; Rogiers, Suzy Y. (Frontiers in Plant Science, 2021)
Vascular bundles in the grape pedicel and berry contain the conduits, phloem and xylem, for transport of water, sugar, nutrients and signals into and through the grape berry and play a critical role in berry growth and composition. Here, we assess the vascular anatomy within the proximal region of the berry. Guided using a 3D berry model generated by micro-CT, differential staining of transverse sections of berries and receptacles was followed by fluorescent microscopy. Morphometric and vascular characteristics were analysed within the central proximal region (brush zone, a fibrous extension from the pedicel vascular system into the berry) of the seeded cultivars Shiraz and Sauvignon Blanc, as well as the stenospermocarpic cultivars Ruby Seedless and Flame Seedless. Observations revealed a change in vascular arrangement from the receptacle into the berry brush zone and differences in xylem element size as well as xylem and phloem area relationships. Xylem anatomical and derived hydraulic parameters, as well as total tissue area of xylem and phloem varied between cultivars and in receptacle and berry components. Variation in vascular growth between grape pedicels and berries was independent of seededness. Differences in receptacle xylem vessel size and distribution could contribute to cultivar-dependent xylem backflow constraint.